STUDI LITERATUR: PELAKSANAAN PELATIHAN TERHADAP PROFESIONALISME GURU IPA DI INDONESIA - Anggun Zuhaida; Yusi Riksa Yustiana (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to describe the design of science teacher training in Indonesia and the results of the training on science teacher professionalism. The method in this research is a literature study using content analysis methods from accredited journal articles and national seminar proceedings consisting of 20 articles from 2015-2022. The study results show that the design of the training that has been carried out has not demonstrated the stages of learning based on the needs and expectations of the Science Teacher but is still focused on delivering the material and not on implementation. The results of the training have not shown a valid measurement because it does not measure the situation at the beginning and end of the teacher during the training process, so it is only seen that there is a positive response and teacher motivation to apply the results of the training.